BAY 94‐9027 prophylaxis is efficacious and well tolerated for up to >5 years with extended dosing intervals: PROTECT VIII extension interim results. Issue 6 (17th October 2019) - Lalezari, Shadan; Reding, Mark T.; Pabinger, Ingrid; Holme, Pal Andre; Negrier, Claude; Chalasani, Pavani; Shin, Ho‐Jin; Wang, Maria; Tseneklidou‐Stoeter, Despina; Maas Enriquez, Monika
Abstract: Introduction: BAY 94‐9027 is an extended‒half‐life, site‐specifically PEGylated, B‐domain‒deleted recombinant factor VIII (FVIII). The PROTECT VIII main study demonstrated efficacy of bleed control using extended‐interval prophylaxis with BAY 94‐9027 for 36 weeks. Aim: To report long‐term efficacy and safety of prophylaxis with BAY 94‐9027 in a descriptive analysis of the ongoing PROTECT VIII extension with a total treatment time of up to >5 years. Methods: Previously treated males aged 12‐65 years with severe haemophilia A who completed the PROTECT VIII main study were eligible for the open‐label extension. Patients received on‐demand treatment or prophylaxis (30‒40 IU/kg twice weekly, 45‒60 IU/kg every 5 days, or 60 IU/kg every 7 days) and could switch regimens as needed. Results: Patients (N = 121; on demand, n = 14; prophylaxis, n = 107) accumulated a median (range) of 3.9 years (297‒1965 days) and 223 (23‒563) total exposure days by 31 January 2018. During the extension, median (quartile [Q]1; Q3) annualized bleeding rates (ABRs) for total bleeds were 1.6 (0.3; 4.6) for patients receiving prophylaxis and 34.1 (20.3; 36.6) for patients receiving on‐demand treatment. ABRs for twice‐weekly (n = 23), every‐5‐days (n = 33), every‐7‐days (n = 23) and variable frequency (n = 28) treatments were 1.7, 1.2, 0.7 and 3.1, respectively. Of prophylaxis patients, 20.6% were bleed‐free throughout the extension (median time, 3.2 years), and 51.0% were bleed‐free during the last 6 months. No patients developed FVIII inhibitors. Conclusions: BAY 94‐9027 prophylaxis was efficacious and well tolerated with dosing intervals up to every 7 days for a median (range) of 3.9 years (0.8‐5.4 years).